Tattoo Fabric: A Trend in Fashionable Textiles - Prosper Kwaku Asiedu; Abigail Anorkor Lartey; Gloria Mawunya Ahorsu; Robert Richard Yao Kpogo (E-Journal of Humanities, Arts and Social Sciences)
Tattoo art has been in existence for ages. They have long served powerful personal and cultural purposes. People wear tattoos for identification, beautification, to express emotions and many more. In recent times, the perception of tattoos has evolved, transforming from static symbols to other forms of self-expression akin to clothing. Tattoo fabric is an innovative trend moving steadily within modern textiles’ scope. It integrates the aesthetics and cultural elements of tattoo art into fabric design and their usage. This paper explores the means of doing tattoo designs in modern times, technological advancements and how they are being worn as fabrics to meet fashionable trends. The study was conducted using the case study approach. Observations, document analysis and semi-structured interviews were used in gathering the data. Fifteen participants were selected for the study. This study gives a clear insight into the potential of tattoo fabrics to redefine the aesthetics and functional aspects of textiles. Thus, some present-day tattoo wearers are not just using their body art for identification; they are also wearing it as clothing. This visual extension of identity adapts to personal, social, and aesthetic contexts and it is now becoming more accepted by many who have sought to use their bodies as canvases for body adornment. The study recommends that this means of self-expression by adorning oneself with tattoos should be closely studied further to find out more modern ways by which mankind is using their artistic skills to express their perceptions in other jurisdictions. Also, stigmatization of tattoo wearers should be reversed and tattoo wearers should consider many fashionable facts before they select their designs.